Internationalism, Democracy, Political Education - Byram, Michael; Golubeva, Irina; Porto, Melina (Taylor & Francis, 2022)
“So Two Cheers for Democracy: one because it admits variety and two because it permits criticism. Two cheers are quite enough: there is no occasion to give three. Only Love the Beloved Republic deserves that” (Forster, 1939). Forster wrote these words in 1939, under the shadow of war with Nazi Germany which, he feared, would destroy democracy and culture. Democracy, he says, deserves one cheer because it starts from the assumption that the individual is important, and that “all types are needed to make a civilisation”. Today we use words such as “multicultural” and “diversity”; Forster uses admirably simple words. Democracy, he says, deserves a second cheer because it allows criticism and, without public criticism, “there is bound to be hushed-up scandal” (1965, p. 77). Such scandals are part of our contemporary experience and the function of the Press – Forster gives it a capital letter – is as important as ever, if not more so.1 Criticism is also a crucial element of the agenda for language teaching which is the focus of this chapter. Our purpose in this chapter is, then, to propose an agenda – “things to be done” – for foreign language education and to demonstrate that the inevitably political nature of education, with its nationalist perspectives, should be enriched by embracing internationalism, a perspective which language teaching is especially able to embody and realize. To do so, we shall first present and discuss some key concepts: internationalism in education, criticality and intercultural citizenship, and competences for intercultural and democratic culture. We shall then present an illustration of these concepts and purposes in a project devised to help learners to respond to the current COVID-19 pandemic.